RANKING OF KEY PERFORMANCE INDICATORS OF THE OVERHAUL PROCESS OF TECHNICAL SYSTEMS - Milovanovic, Vladimir; Aleksic, Aleksandar; Sokolovic, Vlada; Milenkov, Marjan (International Journal of Industrial Engineering: Theory, Applications and Practice, 2024)
The paper presents a developed model for measuring key performance indicators (KPI) of processes implemented in business organizations. The goal of the research is to identify problems that affect the processes through the measurement of KPIs, based on which the management of the organization improves its operations. The model was developed in four phases shown by the algorithm, based on higher-order fuzzy sets, more precisely, using Fermatean fuzzy sets (FFS). The first phase includes decomposing the process into sub-processes using the hierarchy-input-output-processing (HIPO) method and defining KPIs for measurements. In the second phase, the relative importance of sub-processes is determined using the Delphi method extended by FFS. In the third phase, KPIs are assessed at the level of each process by experts. In the fourth phase, KPIs are measured using the VIKOR (Multi-Criteria Optimization and Compromise Solution) method extended by FFS. The model was tested in a business organization that mainly deals with the maintenance of technical military systems. The obtained results confirmed the stability of the model by analyzing the comparison with the results of another method and by analyzing the sensitivity of the change of a certain parameter. The results have been verified in practice by the management of the business organization and, as such, serve for the constant improvement of business.